Lemon verbena nanoemulsion: A natural solution for improving quality and shelf life of Thomson Navel orange (Citrus sinensis L.) - Houshmand Sharafi; Elham Rezaei; Nashmil Farhadi; Abolfazl Alirezalu; Mehran Moradi (Applied Food Research)
The aim of the current study was to evaluate the effect of Lemon verbena essential oil (LVEO) nanoemulsion coating on the postharvest quality of Thomson Navel orange (Citrus sinensis cv. Thomson Navel). Nanoemulsions were prepared using the emulsion phase-inversion method. The effects of nanoemulsion (NL) solutions containing 0.25 % (NL0.25), 0.50 % (NL0.50), 0.75 % (NL0.75), 1.00 % (NL1.00), 1.50 % (NL1.50), and 2.00 % (NL2.00) of LVEO on Thomson Navel fruits were investigated during a 100-day storage under cold conditions. The following results are the notable impact of coating treatments on the phytochemical and antioxidant properties of the Thomson fruit at the end of storage. NL2.00 coated fruits had the lowest pH (3.90 ± 0.03), and highest titratable acidity (0.79 ± 0.05 %), and vitamin C content [45.4 ± 1.6 mg ascorbic acid/100 g fresh weight (FW)] compared to the other treatments. Coated fruits with NL0.75 had the best effect on tannins and carotenoid content, with 1.7 ± 0.1 mg tannic acid equivalent/mL Juice and 227 ± 7 mg/100 mL Juice concentration, respectively. NL0.50-coated fruits showed the highest antioxidant capacity (48.39 %) and total phenolic content [11.6 ± 0.3 mg gallic acid equivalent/100 g fresh weight]. The control group showed higher total soluble solids (16 ± 0.0 %), and NL1.00 treatment was the most beneficial for preserving total flavonoid content (9.1 ± 0.6 mg quercetin equivalent/100 g fresh weight) in coated fruits. Principal component analysis outputs were consistent with our results, indicating that the NL1.00 treatment exhibited the highest total flavonoid content. The hierarchical cluster analysis on day 100 showed fruits treated with NL0.25 and NL0.75 had similar phytochemical and antioxidant parameters to those of the control during the 20-day storage period. The results of this study indicate the potential of LVEO nanoemulsion as a natural preservative for the postharvest storage of fruits.